(untitled) (Proceedings of Faculty of Civil Engineering, 2022)
A bridge is a structure built over existing obstacles. Its construction goes way back to history. The first bridges were built of wood in the form of footbridges. Bridge structures evolved slowly and experientially throughout history and has encountered numerous failures that led to the collapse of the entire bridge or part of its structure. Bridge collapse can be caused by human or natural factors. Human factors include human errors such as errors in design and construction, inadequate maintenance, etc. Natural phenomena include floods, earthquakes, tornadoes, etc. This paper presents the statistics of bridge collapses depending on the location of the bridge, the year of construction and service life duration, the type of construction and material, and the causes of collapse based on a sample of 60 bridges.